Pemanfaatan Nanomaterial dari Limbah Petroleum Coke untuk Meningkatkan Kekuatan Semen Pemboran: Utilization of Nanomaterials from Petroleum Coke to Improve Strength of Drilling Cement - Mursyidah Mursyidah; Idham Khalid; Fitri Mairizki; Rizka Haswinda Putri; Nadhif Akhmarul Asra; Rayendra Maulana Rahman (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Cementing is an important process in oil and gas drilling operations. Its purpose is to isolate zones, withstand formation pressure, and maintain long-term well stability. Therefore, the quality of the cement used must meet the compressive strength (CS) and shear bond strength (SBS) requirements of the American Petroleum Institute (API) standards. Current technology utilizes nanomaterials such as Graphene Oxide Nanosheets (GONs) as an innovative solution to increase the strength of drilling cement. The PKM Team of the Faculty of Engineering, Universitas Islam Riau, held a community service activity at SMK Migas Bumi Melayu Riau to introduce the concept of GONs nanomaterials derived from petroleum coke and how they can increase the strength of drilling cement. This activity is expected to increase teachers' and students' knowledge of the application of nanotechnology in the oil and gas industry and raise awareness of the importance of research and technology in supporting a sustainable oil and gas industry.